POTENSI TUMBUHAN OBAT DI KAWASAN HUTAN TAMAN NASIONAL LORE LINDU (Studi Kasus Desa Namo Kecamatan Kulawi, Kabupaten Sigi) - Hapid, Abdul; Ramlah, Sitti (ForestSains, 2016)
Lore Lindu National Park (LLNP) is one of Biosphere Reserves, the habitat of various types of potential medicinal plants as an asset of biodiversity that should be managed properly for the welfare of the local communities and the ecosystem sustainability. The objective of this study was to determine the potential of medicinal plants in the area of Lore Lindu National Park, precisely in Namo Village, Kulawi Sub-district, Sigi District. Continuous strip sampling was opted as the research method by carrying out purposive sampling in the site where medicinal plants were discovered firstly, by establishing 5 (five) lines with a length of 100 m per line, each line consisted of 4 (four) plots, the distance between the line was 25 m. Total plots were 20 plots with 20 m x 20 m in size per plot. The study found out there were 18 species of medicinal plants that consisted of 14 families in Namo Village, Kulawi, Sigi. The potential of medicinal plants at the tree level is 43 stems / Ha, poles are 40 stems / Ha, sapling are 54 stems / Ha and seedlings and herbs are 296 stems / Ha. Medicinal plant dominated the area at the tree level was Pterospermum celebicum Miq. with Importance Value Index (IVI) of 97.64%, at the pole level of was Huka (Gnetum gnemon L.) with IVI of 84.64%, at the sapling level of Huka (Gnetum gnemon L.) with IVI of 72.69%, and the seedlings and understorey level was Naho (Pandanus sp.) with IVI of 19.50%.